2012
DOI: 10.1111/j.1945-1474.2011.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Language Services Delivery: Findings from a Hospital Quality Improvement Initiative

Abstract: Over 24 million individuals in the United States speak English "less than very well" and are considered limited English proficient (LEP). Due to challenges inherent in patient-provider interactions with LEP patients, LEP individuals are at risk for a wide array of negative health consequences. Evidence suggests that having an interpreter present to facilitate interactions between LEP patients and health professionals can mitigate many of these disparities. This article presents the results and lessons learned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Despite a national mandate for access to interpreter services in settings receiving federal funds [17], under-use of interpreters persists [1825]. While in-person medical interpretation by trained interpreters is considered the gold standard when patient–clinician language concordance is not possible, numerous factors limit use in clinical settings including interpreter staffing and schedules, language requirements, and wait times [20,22,23,26]. Remote methods including telephonic interpretation and videoconferencing medical interpretation (VMI), which allows for two-way audio–visual communication using a mobile unit, are increasingly used to increase access where in-person interpretation is unavailable and/ or where demand is high [23,26].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a national mandate for access to interpreter services in settings receiving federal funds [17], under-use of interpreters persists [1825]. While in-person medical interpretation by trained interpreters is considered the gold standard when patient–clinician language concordance is not possible, numerous factors limit use in clinical settings including interpreter staffing and schedules, language requirements, and wait times [20,22,23,26]. Remote methods including telephonic interpretation and videoconferencing medical interpretation (VMI), which allows for two-way audio–visual communication using a mobile unit, are increasingly used to increase access where in-person interpretation is unavailable and/ or where demand is high [23,26].…”
Section: Introductionmentioning
confidence: 99%
“…The original Speaking Together learning collaborative, a network of 10 hospitals constituting the first national language services QI network (of which SCH was 1), resulted in modest improvements in at least 1 language service process metric per participating hospital, such as screening for preferred language for care. 39 At another institution, installation of standard, dualhandset telephones with easy interpreter access in every hospital room improved provider-reported use of telephone interpretation. 40 These interventions demonstrated improvements in the foundational aspects of providing high-quality language services, namely identifying need and improving access, which are essential first steps.…”
Section: Figurementioning
confidence: 99%
“…Previous studies demonstrated that near 75% of analyzed US hospitals provided medical care for patients who are not native English speakers, while only 18% of surveyed medical facilities validated the level of foreign language proficiency among stuff. [15][16][17][18][19] Based on that, authors resumed that assessment of foreign language skills should be categorized as a mandatory measure within medical educational system, while improvement of such should be provided by specifically design of language training courses. 19 Such English language mastering by individual or group patterns together with English language curriculum classes could improve the overall quality of dental and medical education among foreign students.…”
Section: Resultsmentioning
confidence: 99%